2002
DOI: 10.1149/1.1421746
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of ZnSe-Fe and ZnSe-Co Granular Films

Abstract: ZnSe-Fe and ZnSe-Co granular films have been successfully obtained by electrodeposition under potentiostatic conditions. Cyclic voltammograms of the solutions containing all precursors of the systems are consistent with anomalous codeposition of the zinc and iron-group metals. Electron microscopy analyses reveal a network of Fe and Co particles dispersed in polycrystalline ZnSe without evidence of intermediate compound formation.Electrochemical deposition is an attractive approach for growing semiconductor com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…5 However, selenium oxide and quasiamorphous selenium was also observed. 18 Progressive accumulation of Se onto practically stoichiometric ZnSe was revealed by photoemission depth profiling.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5 However, selenium oxide and quasiamorphous selenium was also observed. 18 Progressive accumulation of Se onto practically stoichiometric ZnSe was revealed by photoemission depth profiling.…”
Section: Resultsmentioning
confidence: 99%
“…Voltammetry studies have shown that when the applied potential is scanned toward negative values in the solutions containing all chemical precursors a complex reduction wave is obtained. 18 The presence of iron and cobalt in the solution even at low concentrations significantly changes the deposition process. It seems that anomalous codeposition of zinc and iron-group metals [21][22][23] becomes predominant with a reduction potential shift to negative values compared to their standard redox potential.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations